Mapping the fluctuating effect of strategy use ability on English reading performance for nursing students: A multi-layered moderation analysis approach. (April 2020) - Cai, Yuyang; Kunnan, Antony John
An essential hypothesis of modern language assessment theory pertains to the interaction between strategy use ability (strategic competence) and second language knowledge. However, how they interact with each other is rarely explored. Drawing on relevant research in the literature, in this paper we proposed three interaction patterns (i.e., linear, quadratic, and cuboid) in which language knowledge moderates the effect of strategy use ability on L2 reading performance. A pool of 1491 nursing students were invited to respond to three instruments, each measuring language knowledge, strategy use ability, and nursing English (L2) reading ability, respectively. Student responses were first scored using multidimensional item response theory (MIRT). Next, we applied multi-layered moderation analysis (MLMA) to these MIRT-based scores to detect the hypothetical interaction patterns. The results supported the cuboid interaction pattern or, metaphorically, the pattern of an island ridge curve (IRC). Substantially, this indicated that the effect of strategy use ability on nursing English reading performance fluctuated in a down-up-down pattern with the increase of students' language knowledge. Our study also revealed different patterns of strategy use depending on students' language knowledge level.